Integrated Covalent Organic Framework/Carbon Nanotube Composite as Li‐Ion Positive Electrode with Ultra‐High Rate Performance. Issue 39 (12th September 2021) - Gao, Hui; Zhu, Qiang; Neale, Alex R.; Bahri, Mounib; Wang, Xue; Yang, Haofan; Liu, Lunjie; Clowes, Rob; Browning, Nigel D.; Sprick, Reiner Sebastian; Little, Marc A.; Hardwick, Laurence J.; et al.
Abstract: Covalent organic frameworks (COFs) are promising electrode materials for Li‐ion batteries. However, the utilization of redox‐active sites embedded within COFs is often limited by the low intrinsic conductivities of bulk‐grown material, resulting in poor electrochemical performance. Here, a general strategy is developed to improve the energy storage capability of COF‐based electrodes by integrating COFs with carbon nanotubes (CNT). These COF composites feature an abundance of redox‐active 2, 7‐diamino‐9, 10‐phenanthrenequinone (DAPQ) based motifs, robust β‑ketoenamine linkages, and well‐defined mesopores. The composite materials (DAPQ‐COFX—where X = wt% of CNT) are prepared by in situ polycondensation and have tube‐type core‐shell structures with intimately grown COF layers on the CNT surface. This synergistic structural design enables superior electrochemical performance: DAPQ‐COF50 shows 95% utilization of redox‐active sites, long cycling stability (76% retention after 3000 cycles at 2000 mA g −1 ), and ultra‐high rate capability, with 58% capacity retention at 50 A g −1 . This rate translates to charging times of ≈11 s (320 C), implying that DAPQ‐COF50 holds excellent promise for high‐power cells. Furthermore, the rate capability outperformed all previous reports for carbonyl‐containing organic electrodes by an order of magnitude; indeed, this power density and the rapid (dis)charge time are competitive with electrochemical capacitors. Abstract : Composites of a redox‐active covalent organic framework intimately grown around carbon nanotubes that were used as the positive electrode in Li‐ion cells are reported. The optimized composite material has a tube‐type core‐shell structure and retains 58% of its capacity at 50 A g −1 . This rate translates to charging times of ≈11 s (320 C).